Peran Media Digital Dalam Strategi Komunikasi Pemasaran Lembaga Filantropi Islam Di Indonesia - Arina Muntazah; Rosiana Andhikasari (CV. ITTC INDONESIA, 2021)
The existence of Islamic Philanthropic Institutions in Indonesia is now increasingly recognized by the public, not a few people who distribute donations and zakat, infaq, sodqqo and waqf (ZISWAF) through these institutions. With the development of the times, the marketing communication strategy of Islamic philanthropic institutions in Indonesia cannot be separated from the role of digital media. This study intends to identify and describe the role of digital media in the implementation of marketing communication strategies at Islamic Philanthropic Institutions in Indonesia. Based on the research results, DIMC or Digital Integrated Marketing Communication activities which consist of digital advertising, digital sales promotion, digital personal selling, digital direct marketing, and digital public relations are carried out by utilizing digital media in the form of websites, e-mails mobile applications, and social media such as Instagram, Facebook, WhatsApp and YouTube.